2009
DOI: 10.1016/j.febslet.2009.07.061
|View full text |Cite
|
Sign up to set email alerts
|

The polyketide cyclase RemF from Streptomyces resistomycificus contains an unusual octahedral zinc binding site

Abstract: a b s t r a c tRemF is a polyketide cyclase involved in the biosynthesis of the aromatic pentacyclic metabolite resistomycin in Streptomyces resistomycificus. The enzyme is a member of a structurally hitherto uncharacterized class of polyketide cyclases. The crystal structure of RemF was determined by SAD and refined to 1.2 Å resolution. The enzyme subunit shows a b-sandwich structure with a topology characteristic for the cupin fold. RemF contains a metal binding site located at the bottom of the predominantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 33 publications
2
27
0
Order By: Relevance
“…The protein data bank contains few examples of first-row transition metals bound to native His 4 sites, which include a manganese-containing photochemical reaction center from Rhodobacter spaeroides Y , 53 a manganese-containing cupin from Thermotoga maritima , 54 and RemF, a polyketide cyclase from Streptomyces resistomycificus crystallized in the zinc-bound form. 55 These structures exhibit six-coordinate M(II) centers. Recent crystallographic studies of S100B revealed pH-dependent ligand swapping and tetrahedral Zn(II) coordination to four His residues at pH 9 whereas the metal ion was coordinated to a His 3 Asp motif at lower and higher pH values.…”
Section: Discussionmentioning
confidence: 99%
“…The protein data bank contains few examples of first-row transition metals bound to native His 4 sites, which include a manganese-containing photochemical reaction center from Rhodobacter spaeroides Y , 53 a manganese-containing cupin from Thermotoga maritima , 54 and RemF, a polyketide cyclase from Streptomyces resistomycificus crystallized in the zinc-bound form. 55 These structures exhibit six-coordinate M(II) centers. Recent crystallographic studies of S100B revealed pH-dependent ligand swapping and tetrahedral Zn(II) coordination to four His residues at pH 9 whereas the metal ion was coordinated to a His 3 Asp motif at lower and higher pH values.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has only 40% sequence identity to GtHNL. The other structures showed even lower similarity [1VJ2: Z-score 14.5, RMSD 1.9, 20% sequence identity; 1O4T: Z-score 14.5, RMSD 2.0, sequence identity 21% (both uncharacterized monocupins from Thermotoga maritima); 3HT2: Z-score 14.5, RMSD 2.4, 14% sequence identity (a zinc-containing polyketide cyclase RemF from Streptomyces resistomycificus [22])]. The gene corresponding to 2F4P was obtained as a synthetic gene and re-cloned, and the protein was expressed as described for GtHNL, but showed only very weak hydroxynitrile lyase activity, which was not investigated any further (data not shown).…”
Section: Overall Three-dimensional Structure Of Gthnlmentioning
confidence: 99%
“…Other enzymes with a "reduction" of the 3His-1Glu motif are the gentisate 1,2-dioxygenases (GDOs) and 3-hydroxyanthranilate 3,4-dioxygenases (HADs) (see below). Most remarkably, the metal binding site in polyketide cyclase RemF, a monocupin protein, contains an octahedral zinc site, with four histidine residues as protein ligands to the Zn 2ϩ ion (110).…”
Section: Fig 2 Ribbon Diagram Of the Monomer Of Quercetinase Of A Jamentioning
confidence: 99%